HUBUNGAN JENIS KELAMIN, USIA, TINGGI SADEL DAN DURASI PESEPEDA TERHADAPAT RESIKO TERJADINYA NYERI PUNGGUNG BAWAH - Febriani, Yelva; Segita, Riri; Olyverdi, Reza (PHYSIO MOVE JOURNAL, 2022)
ABSTRACT :According to Clarsen et al (2010) back pain is a disease that usually felt by cyclists, in his research 45% of professional cyclists experienced low back pain barriers and 20% reduced cycling activities to recover low back pain. Based on observations, it was found that the bikes of paliko bicycle club felt pain in the back to the foot area when playing a bicycle. The purpose of the study was to determine Factors Related to Lower Back Pain in Bikers of Paliko Payakumbuh 2021 Cyclist. The type of this study was descriptive analytic with cross sectional approach. The population was all members of the Bikes of Paliko bicycle club. By using total sampling technique, 30 people were chosen as the samples. The data were collected through questionnaires and it was analyzed by univariate analysis.The results of the univariate study showed that 10 (33.3%) respondents said they had mild pain in low back pain, 15 (50%) had moderate pain and 5 (16.7%) had  severe pain, 20 (66.7%) were men and 10 (33.3%) were female, 16 (53.3%) were adolescent age and 14 (46.7%) were adult age, 22 (73.3%) non-ergonomic saddle height and 8 (26.7%) ) ergonomics, 4 (13.3%) short duration and 26 (86.7%) long. Then, there was a significant relationship between saddle height and the occurrence of low back pain in cyclists (p-value 0.043) and there was no relationship between gender (p-value 0.223), age (p-value 0.765) and duration (p-value 0.562) with lower back pain.From the results of the study, it can be concluded that there was a relationship between saddle height and low back pain in cyclists and there was no relationship between gender, age and duration of occurrence of low back pain in cyclists at the Bikes of Paliko Payakumbuh Bike Club 2021.Keywords                     : Low Back Pain, Gender, Age, Saddle Height and Duration.